Aplicação SIG ao Ordenamento do Território na frente urbana de Espinho : uma previsão baseada na análise histórica da dinâmica costeira : a prediction based on historical analysis of coastal dynamics - Pires, Ana (2007)
This study was based on a historical research and a detailed analysis of aerial photos of the littoral of Espinho (NW Portugal), as well as on field inquiries to the local population. The data gathered allowed an analysis of the Espinho dynamic coastal system since the XIX Century, and the inference of its evolution as a useful tool for the management of the coastal urban landscape. A historical reconstitution of the location of coastal protection structures was first carried out, which comprised a cartographic representation of buildings, streets and sea line invasions. Actual and historical events related to coastal erosion and urban landscape management were geo-referenced and represented by using GIS (geographical information systems) tools. The use of an interactive interface provided a simple and easy way to perform queries on the existence and occurrence of coastal protection structures since 1889. Susceptibility maps of sea invasions were then produced through spatial analysis. Finally, the knowledge on these past events was used to predict the location of the actual coastal line if no groins had been constructed. The present study takes advantage of GIS tools to contribute to the understanding of the geomorphological dynamics of Espinho. Furthermore, it provides a sound basis for monitoring and management of the coastal zone, namely in what respects the planning of security measures concerning the eventual occurrence of disastrous scenes of sea invasions.